2008
DOI: 10.1111/j.1440-1843.2008.01356.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms of microsomal epoxide hydrolase and COPD: Results from meta‐analyses

Abstract: Association between polymorphisms of microsomal epoxide hydrolase and COPD: Results from meta-analyses HU G, SHI Z, HU J, ZOU G, PENG G, RAN P. Respirology 2008; 13: 837-850 Background and objective: COPD is a complex polygenic disease in which gene-environment interactions are very important. The gene encoding microsomal epoxide hydrolase (EPHX1) is one of several candidate loci for COPD pathogenesis and is highly polymorphic. Based c on the polymorphisms of EPHX1 gene (tyrosine/histidine 113, histidine/argin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 37 publications
4
30
1
4
Order By: Relevance
“…One study found an association of the 113C allele with functional impairment in COPD [35]. Some studies indicate a protective effect of the putative fast 139G allele [1,28]; however, many studies find no effect at all of either polymorphism [7,22,36]. Similar disparities are found in studies investigating association of COPD with EPHX1 phenotype [7,21,22,36].…”
Section: Copdmentioning
confidence: 79%
“…One study found an association of the 113C allele with functional impairment in COPD [35]. Some studies indicate a protective effect of the putative fast 139G allele [1,28]; however, many studies find no effect at all of either polymorphism [7,22,36]. Similar disparities are found in studies investigating association of COPD with EPHX1 phenotype [7,21,22,36].…”
Section: Copdmentioning
confidence: 79%
“…But still the treatment tools, available to date, are insufficient to perform panacea of the disease. Studies that have been implicated the oxidative stress as a crucial impact factor in lung inflammatory pathways and COPD concluded that several antioxidant genes such as gst (gstm1, gstt1 and gstp1), microsomal epoxide hydrolase 1 (mephx1) [15][16][17][18] and Klotho gene [52] exert an important role regarding the rapid decline in pulmonary function. However, some inconclusive results drawn out from previous studies are due to diversities in population that have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Hu G. et al in a study reviewing meta analysis results concerning the association of antioxidant genes in pathogenesis of COPD, concluded that EPHX1 113 and EPHX1 139 are both genetically relative factors for susceptibility of COPD in Asian population, especially the fast activity phenotype EPHX1.This observation did not appeared in Caucasians who are more susceptible in the risk for developing COPD concerning the slow activity phenotype of the EPHX 1 in contrast to the Asians. These facts underline that the susceptibility in COPD depends upon the diverse ethnic gene-environment interactions [17]. Analyses the same aspect of the oxidative stress and the plausible role of the EPHX 1 as a protective mechanism against it Lakhdar R. et al in an association study concluded in weak association of the EPHX 1 113His genotype and no association with the EPHX 139His genotype in Tunisians, when adjusted on the basis of phenotypical appearance of the disease [18].…”
Section: Genes and Oxidative Stressmentioning
confidence: 99%
“…Затем, в процессе 2 й фазы, эти про межуточные метаболиты с помощью ферментов семейств глутатионтрансфераз, УДФ глюкуронсуль фотрансфераз, N ацетилтрансфераз превращаются в водорастворимые нетоксичные продукты и выво дятся из организма. Известны 2 функционально зна чимых полиморфизма гена EPHX1 в 3 м (Т 337С) и 4 м (A 415G) экзонах, приводящие к аминокис лотным заменам Y113H (T>C) и H139R (A>G) соот ветственно, что изменяет свойства фермента [13]. По лиморфизм Т 337С ответственен за снижение активности фермента на 50 % ("медленный" аллель), а полиморфизм A 415G -за повышение активности примерно на 25 % ("быстрый" аллель).…”
Section: заметки из практикиunclassified
“…Можно полагать, что факторами, способ ствующими развитию токсического гепатита, явились комбинированная антибактериальная терапия, нали чие тяжелой респираторной вирусной инфекции, на личие гепатита А в анамнезе, а также полиморфизм в гене микросомальной эпоксидгидролазы (EPHX1 Y113H TC). Как известно, данный полиморфизм спо собен нарушать процесс биотрансформации ксено биотиков (в т. ч. антибактериальных препаратов), что может усиливать их токсическое действие [13].…”
Section: заметки из практикиunclassified